Postharvest losses to agricultural product traders in Mutare, Zimbabwe - Chebanga, Fungisai; Mukumbi, Kudzai; Moses, Mutetwa; Mtaita, Tuarira (Journal of Scientific Agriculture, 2018)
The study examined the nature and causes of postharvest losses incurred by formal and informal traders in Mutare urban. A survey was conducted where questionnaires were administered to various respondents in the formal and informal sector of fruits and vegetables. The research study assessed the profitability of trading in fruits and vegetables to formal and informal traders. It also assessed traders’ perception of the losses of fruits and vegetables and further determined the possible ways of reducing these postharvest losses so as to enhance profitability in the sector. The study from a sample of 34 respondents revealed that both formal and informal traders experience losses during storage and transportation of goods. Losses incurred during storage were due to the unavailability of proper storage facilities specifically to informal traders. Furthermore, postharvest losses were also resulting from excessive exposure of crops to sunlight, poor packaging, poor carrying containers, attacks by insect pests as well as microbial or disease attacks. Postharvest losses affect profitability and growth of the fruits and vegetables sectors. There is need for farmers to improve on the quality of their produce and harvesting practices as emphasized by traders as they suffered losses as a result of poor quality goods supplied. Further postharvest practices should be improved by traders with special emphasis on adequate storage, handling and proper transportation of goods.